GAYA KOMUNIKASI KEPEMIMPINAN PEREMPUAN: (Studi Kualitatif Deskriptif dr. Hj. Cellica Nurrchadiana Sebagai Bupati Kabupaten Karawang Dari Perspektif Ilmu Komunikasi) - Nur Ratih Devi Affandi; Yusuf Hartawan; Laila Zainab Al Aqilah (Ilmu Komunikasi, FISIP Universitas Pasundan, 2022)
ABSTRACT This study aims to determine the Communication Style of Women's Leadership conducted by dr. Hj. Cellica Nurrchadiana as the first female regent in Karawang district through the style of delivering messages either publicly or privately to members or the community which is considered quite successful, as evidenced by her re-election by a landslide in winning the 2020 pilkada as regent in the second period. The researcher found that the communication style of women's leadership carried out by Cellica nurrchadiana as the regent of Karawang was that the communication style of the Regent of Cellica was influenced by the situation at hand. The Regent of Cellica will use different communication styles when in Public, Private, Storytelling, Listening, Asking Questions, and Conflict situations that are conveyed to fellow officials, members or the public which are considered appropriate in accordance with the proportion of messages and interesting delivery methods so that they can well received by the communicant.